Epigenetic Reprogramming Mediated by Maternal Diet Rich in Omega-3 Fatty Acids Protects From Breast Cancer Development in F1 Offspring - Abbas, Ata; Witte, Theodore; Patterson, William L.; Fahrmann, Johannes F.; Guo, Kai; Hur, Junguk; Hardman, W. Elaine; Georgel, Philippe T. (Frontiers in Cell and Developmental Biology, 2021)
Diets rich in omega-3 fatty acids have been associated with lowered risks of developing certain types of cancers. We earlier reported that in transgenic mice prone to develop breast cancer (BCa), a diet supplemented with canola oil, rich in omega-3-rich fatty acids (FA) (as opposed to an omega-6-rich diet containing corn oil), reduced the risk of developing BCa, and also significantly reduced the incidence of BCa in F1 offspring. To investigate the underlying mechanisms of the cancer protective effect of canola oil in the F1 generation, we designed and performed the present study with the same diets using BALB/c mice to remove any possible effect of the transgene. First, we observed epigenetic changes at the genome-wide scale in F1 offspring of mothers fed diets containing omega-3 FAs, including a significant increase in acetylation of H3K18 histone mark and a decrease in H3K4me2 mark on nucleosomes around transcription start sites. These epigenetic modifications contribute to differential gene expressions associated with various pathways and molecular mechanisms involved in preventing cancer development, including p53 pathway, G2M checkpoint, DNA repair, inflammatory response, and apoptosis. When offspring mice were exposed to 7,12-Dimethylbenz[a)anthracene (DMBA), the group of mice exposed to a canola oil (with omega 3 FAs)-rich maternal diet showed delayed mortality, increased survival, reduced lateral tumor growth, and smaller tumor size. Remarkably, various genes, including BRCA genes, appear to be epigenetically re-programmed to poise genes to be ready for a rapid transcriptional activation due to the canola oil-rich maternal diet. This ability to respond rapidly due to epigenetic potentiation appeared to contribute to and promote protection against breast cancer after carcinogen exposure.